Transparent nature-based luminescent solar concentrator with NIR emission and integrated thermal sensing - Correia, Sandra F. H. (2025)
The engineering of luminescent solar concentrators (LSCs) offers a way to turn windows into energy-generating units while maintaining transparency. Through UV/blue down-shifting materials to the red/near-infrared (NIR) spectral region, the performance of building integrated photovoltaics is maximized without compromising indoor light quality. The most efficient solutions are based on quantum dots, which raise environmental concerns. To address this, natural renewable materials, like bacteriochlorophyll (BChl) from phototrophic bacteria were used to fabricate an LSC prototype dispersed in a styrene-ethylene-butylene-styrene (SEBS) matrix. The LSCs emit in the red/NIR region with an emission quantum yield of ∼7%, demonstrating external photon efficiency and electrical device efficiency values of ∼1.0% and ∼0.04%, respectively. The thermal dependence of the BChl/SEBS emission is used to set two independent thermometric parameters based on the emission and the electrical power generated by the LSC edge-mounted photovoltaic cells with relative sensitivity values up to ∼2% °C−1, which is a remarkable performance. This prototype was scaled up for an active area of 0.1 m2, representing the first large-area LSC using nature-based red/NIR emission centers.